2017
DOI: 10.1177/2396941516684834
|View full text |Cite
|
Sign up to set email alerts
|

The primary-to-secondary school transition for children on the autism spectrum: A multi-informant mixed-methods study

Abstract: Background and aims: Children diagnosed with an autism spectrum condition are known anecdotally to be especially vulnerable during the transition to secondary school. Yet, very little is known about the child-, school-and system-level factors that can potentially make changing schools particularly difficult for these children. Here, we report on a mixedmethod study, which examined the factors that influence a successful school transition for autistic children in one local education authority in England. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
128
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(140 citation statements)
references
References 40 publications
(72 reference statements)
10
128
0
2
Order By: Relevance
“…The current findings suggest that autistic girls may benefit from mental health and social support from the beginning of the transition to secondary school, a time that is widely recognised by researchers, educators and parents as especially challenging for young autistic people (Ashburner, Ziviani, & Rodger, 2010;Makin, Hill, & Pellicano, 2017;Sproston et al, 2017). This transition may be particularly difficult for autistic girls, however, as they face a significant jump in what is expected of them socially in adolescence, with peers suddenly communicating in more sophisticated and complex ways, alongside managing the practicalities of high school that are described by autistic boys in the existing literature (Humphrey & Lewis, 2008;Makin et al, 2017). Although our data cannot speak to the potential similarities and differences in the school transition experiences of autistic girls and boys, as we did not interview the parents of autistic boys, this would be an important focus for future research.…”
Section: Discussionmentioning
confidence: 81%
“…The current findings suggest that autistic girls may benefit from mental health and social support from the beginning of the transition to secondary school, a time that is widely recognised by researchers, educators and parents as especially challenging for young autistic people (Ashburner, Ziviani, & Rodger, 2010;Makin, Hill, & Pellicano, 2017;Sproston et al, 2017). This transition may be particularly difficult for autistic girls, however, as they face a significant jump in what is expected of them socially in adolescence, with peers suddenly communicating in more sophisticated and complex ways, alongside managing the practicalities of high school that are described by autistic boys in the existing literature (Humphrey & Lewis, 2008;Makin et al, 2017). Although our data cannot speak to the potential similarities and differences in the school transition experiences of autistic girls and boys, as we did not interview the parents of autistic boys, this would be an important focus for future research.…”
Section: Discussionmentioning
confidence: 81%
“…It should be noted that attendance cannot be a proxy for engagement and motivation, and neither can we assume that a child who is attending classes regularly is experiencing positive transitions. It is also worth noting that Makin et al () reported that students with additional support needs (n = 15) had negative school experiences, regardless of the type of educational establishment they moved to, suggesting that these children’s needs were not met, whether they attended a mainstream or special school.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of researchers appear to have focused on the challenges associated with transition, such as the negative impact on academic grades (Hopwood, Hay, & Dyment, ) and psychological wellbeing (Jackson & Schulenberg, ), an increase in externalizing behaviours (Palmu, NĂ€rhi, & Savolainen, ) and less positive attitudes towards subjects (e.g., Mathematics, GarcĂ­a, RodrĂ­guez, Betts, Areces, & GonzĂĄlez‐Castro, ). Authors have highlighted the particular challenges faced by children and young people considered more vulnerable during transition, such as those with additional support needs, due to heightened anxiety (Peters & Brooks, ; Mandy, Murin, Baykaner, Staunton, Cobb, et al, ; Mandy, Murin, Baykaner, Staunton, Hellriegel, et al, ; Makin, Hill, & Pellicano, ). However, some authors have challenged the emphasis on the negative features of moving to secondary school and propose counterbalancing this with positive aspects, such as increased subject choices in secondary school (Jindal‐Snape & Foggie, ; Jindal‐Snape, ; Jindal‐Snape & Cantali, ; Jindal‐Snape, Cantali, MacGillivray & Hannah, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a strong need to focus research efforts on girls and women on the autism spectrum (Pellicano et al, 2014), inappropriate school environments, a lack of staff understanding and breakdowns in relationships have been repeatedly raised by parents and young autistic people (mostly boys) in other studies, albeit in different environments (e.g. Brede et al, 2016;Makin et al, 2017). Future studies could investigate if/how variables such as social anxiety and friendship affect exclusion in girls compared to boys, as while the overall themes may be similar, the fine-grained content may differ.…”
Section: Discussionmentioning
confidence: 99%
“…Humphrey and Lewis (2008), for example, found that anxiety, sensory-sensitivities, bullying and low selfimage contributed to negative secondary school experiences in their sample of 20 autistic boys. More recently, Dillon, Underwood and Freemantle (2016) reported how 14 autistic secondary school students (11 boys, 3 girls) were positive about their environment and appreciated good relationships with staff; reiterating how calmer atmospheres and positive staff-pupil relationships are potentially crucial to inclusion (Brede et al, 2016;Lloyd & O'Regan, 1999;Makin, Hill & Pellicano, 2017;Michael & Frederickson, 2013;Robertson, Chamberlain, & Kasari, 2003).…”
mentioning
confidence: 99%